2007
DOI: 10.1097/01.prs.0000260703.56453.06
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Surgical Release of Ipsilateral Pronator Teres and Carpal Tunnel Syndromes

Abstract: The main benefit of using this protocol in this selected group of patients is to shorten total morbidity time and to avoid exposure of the patient to two operations instead of one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…Our previous study reported 55 patients in whom both lesions were suspected and they underwent simultaneous release of the ipsilateral pronator and carpal tunnel. Benefits of this protocol were limited exposure for two operations, shortened morbidity time and provided satisfactory outcome (86% improved symptom and 65% complete recovery) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported 55 patients in whom both lesions were suspected and they underwent simultaneous release of the ipsilateral pronator and carpal tunnel. Benefits of this protocol were limited exposure for two operations, shortened morbidity time and provided satisfactory outcome (86% improved symptom and 65% complete recovery) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms were resolved in 8 forearms: reduced (n = 20), persistent (n = 5), and unchanged (n = 3). 3 Mujadzic et al 25 evaluated 61 patients following release of the lacertus fibrosus, PT, and the FDS arch and reported complete relief in 39 patients. In a previous anatomical study, the FDS arch was found to be tendinous in most cases with direct fibrous attachments to the underlying median nerve and increased compression seen with forearm extension.…”
Section: Discussionmentioning
confidence: 99%
“…46) If there is tenderness at the proximal forearm and sensory changes are found in the palm and the first three fingers, pronator teres syndrome should be also considered. 47) Concomitant ulnar or cubital tunnel syndrome should be considered if signs include first dorsal interosseous weakness or tingling in the fourth and fifth digits. 1,2) Raynaud’s phenomenon—vibration white finger—should be considered if the patient has a history of exposure to cold temperatures or vibration.…”
Section: Differential Diagnosis Of Ctsmentioning
confidence: 99%